(untitled) (Ius Novum, 2022)
In the ongoing climate crisis, more and more states of the world undertake initiatives that would reduce negative impact of dangerous growth of global average temperature, including droughts, drowning of coastal cities and water shortage. Recently, an ambitious idea to provide huge supplies of water for the population of the United Arab Emirates was initiated by one of Emirati businessmen – Mr Abdulla Alsheni, who plans to tow a huge Antarctic iceberg to the coast of Emirates. The plan itself is a logistic challenge, but at the same time may raise certain concerns on its compliance with international law. Hereby article has as an aim response to a question whether an act of towing an Antarctic iceberg would breach international law provisions, particularly those related to Antarctic Treaty System and law of the seas.